Market-oriented urban and peri-urban dairy systems - Tegegne, Azage; Tadesse, M.; Yami, A.; Mekasha, Yoseph (2000)
Urban and peri-urban dairy production systems are among the many forms of dairy production systems in the tropics and sub-tropics. The systems involve the production, processing and marketing of milk and milk products that are channelled to consumers in urban centres (Rey et al., 1993; Staal and Shapiro, 1996). These urban and peri-urban dairy production systems evolved to satisfy the increasing demand for milk in urban centres as a consequence of increasing urbanisation, rising per capita income and increasing cost of imported milk and milk products. They contribute to overall development through income and employment generation, food security, asset accumulation, poverty alleviation and improving human nutrition and health. A study on market-oriented urban and peri-urban dairy production systems in the Addis Ababa milk shed was undertaken, to test a conceptual framework, developed by ILRI for general characterisation of dairy systems, characterisation of specific sub-systems and identification of major constraints. A total of 147 dairy farms (market-oriented smallholder and commercial) were selected for characterisation, and of the three urban systems 49 farms for a further detailed study. Topics of discussion include traditional crop (livestock farms in rural areas; intensified dairy) crop livestock farms; peri-urban farms in secondary towns; intra-urban dairy farms in Addis Ababa; and urban dairy in secondary towns. Constraints and opportunities for development are also examined.